Let y = (In x)^2. This is a function of a function.
Use the chain rule to find dy/dx
Let In x = u, then y = u^2.
dy/dx = 2u = 2 In x = Inx^2
and du/dx = 1/x.
Hence dy/dx = dy/du times du/dx = Inx^2 times 1/x
= (Inx^2)/(x) *brackets added for clarity.
2006-10-29 19:31:16
·
answer #1
·
answered by Anonymous
·
1⤊
8⤋
Differentiate Ln X 2
2016-11-02 11:17:38
·
answer #2
·
answered by ? 4
·
0⤊
0⤋
I think you'd have to use the chain rule. Differentiate ln x, which is 1/x, and then suppose your other function is x^2. Thus, dy/dx = (dy/du)(du/dx). Thus, do 2(ln x)(1/x). I think....
2006-10-29 13:24:25
·
answer #3
·
answered by Carrot, the Peanut 1
·
6⤊
1⤋
For this problem you use the chain rule.
the answer is 2*ln x * (1/ x) = 2(ln x) / x.
good luck
2006-10-29 13:25:00
·
answer #4
·
answered by Anonymous
·
3⤊
1⤋
y=[lnx]^2
y'=2lnx*1/x
=2 lnx/x
2006-10-30 00:41:27
·
answer #5
·
answered by openpsychy 6
·
0⤊
1⤋
Answer = (2/x) ln(x)
2006-10-29 13:25:01
·
answer #6
·
answered by turkeyphant 3
·
0⤊
2⤋
dy/dx=xd/dx2^(x)+ 2^(x) d/dx(x) = x.2^(x).log2 +2^(x) therefore dy/dx =2^(x)[xlog2+1]
2016-03-17 05:52:02
·
answer #7
·
answered by Anonymous
·
0⤊
0⤋
here we use the chain rule
d(uv)/dx=(u)dv/dx+(v)ud/dx.(1)
let y=(lnx)^2, =lnx*lnx, u=lnx,v=lnx
substitute into (1)
d(lnx*lnx)/dx= lnx*1/x+lnx*1/x
=(2lnx)/x
i hope that this helps
2006-10-29 19:48:06
·
answer #8
·
answered by Anonymous
·
1⤊
1⤋
(ln(x))^2 = (ln(x)) * (ln(x))
(ln(x)')(ln(x)) + (ln(x))(ln(x))'
(1/x)(ln(x)) + (ln(x))(1/x)
(ln(x)/x) + (ln(x)/x)
(2ln(x))/x or (ln(x^2))/x
2006-10-29 15:04:07
·
answer #9
·
answered by Sherman81 6
·
3⤊
1⤋